IMPACT OF PRENATAL ADMINISTRATION OF MELAMINE ON FOETAL GROWTH IN RATS - Tayem, Yasin; Veeramuthu, Sindhan; Rashid, Aisha; Sequeira, Reginald; Fadel, Raouf (Journal of Ayub Medical College Abbottabad, 2019)
Background: Data on the potential effects of maternal exposure to melamine is scarce. We aimed to evaluate the impact of melamine administration on pregnancy outcome and foetal growth in rats. Methods: Positively-mated female Sprague-Dawley rats (n=24) were treated from day 6to day 20of gestation with vehicle (control), melamine 300 mg/kg/day (group-1) or melamine 450 mg/kg/day (group 2). On day 21, the numbers of foetal resorptions and dead foetuses were recorded. Thereafter, pups were examined for external anomalies, and various growth parameters were measured. Results: A remarkable increase in the number of resorptions was observed in group-2 compared to the other two groups. A significant increase in foetal weight and placental weight was seen in group-2 compared to control. Head length and placental diameter were low in group-1 compared to control. The ratio between crown-rump length and head length was significantly greater in group 2 compared to control indicating asymmetrical intrauterine growth restriction. The only influence observed in group 1 compared to control was a decrease in placental diameter. No gross foetal malformations or changes in umbilical cord length, crown-rump length or biparietal diameter were observed in both melamine-treated groups. Conclusions: Maternal exposure to melamine during pregnancy increased the incidence of resorption and resulted in asymmetrical intrauterine growth restriction. Keywords: Melamine; Maternal Exposure; Foetal Growth; Rat